Aligning Purchasing Strategy with Supply Chain Strategy: A case study of a Malaysian Foodservice Equipment Distributor - Chee, Wen Zhi (2015)
The role of purchasing in the management of supply chain has proven to be important in today’s ever demanding business environment. The dissertation focuses on aligning purchasing strategy with supply chain strategy by comparing theory with practice, and determine any linkage between purchasing strategy with supply chain strategy. The overall focus of this research is to advance and find a linkage between Kraljic’s purchasing portfolio model and Hau Lee’s uncertainty framework. This dissertation met this aim through an extensive study of relevant literature and the implementation of a case study. This case study with F&B Facilities Sdn. Bhd. will be conducted mainly through two mediums: structured interview and secondary data collection. The research findings indicates that there are significant linkages between purchasing strategy and supply chain strategy through the usage of Kraljic’s purchasing portfolio model and Hau Lee’s uncertainty framework. However, the application of this analysis is not a standardized blue print that can be followed by other companies. It requires reflecting on results and critical thinking to attain a meaningful and useful outcome.